Cylindrospermopsin impairs vascular smooth muscle cells by P53-mediated apoptosis due to ROS overproduction. (15th December 2021) - Zhang, Qian; Wang, Linping; Chen, Guoliang; Wang, Mingxing; Hu, Tingzhang
Graphical abstract: Highlights: Cylindrospermopsin decreased VMSC viability and inhibited VMSC migration. Cylindrospermopsin impaired DNA and cytoskeleton and changed VMSC morphology. Cylindrospermopsin promoted VMSC apoptosis through P53 signaling pathways. Cylindrospermopsin induced reactive oxygen species overproduction in VMSCs. Cylindrospermopsin may induce vascular developmental defects. Abstract: Cylindrospermopsin (CYN) is a toxic secondary metabolite from cyanobacteria that can cause cardiovascular disease. However, the study of CYN-induced cardiovascular toxicity in vitro is very limited and the mechanism is remain to be clarified. Vascular smooth muscle cells (VMSCs) have an important function in maintaining the structural and functional integrity of the aortic wall, and are an important in vitro model for cardiovascular research. Thus, the effects of CYN exposure (2, 20, 200, and 2000 nM) on VMSCs were analyzed. In vitro study, results showed that CYN exposure decreased VMSCs viability, inhibited VMSCs migration, induced DNA damage, destroyed cytoskeleton, changed cell morphology, promoted VMSCs apoptosis, and increased intracellular reactive oxygen species (ROS) levels. In addition, CYN could induce the activities of SOD, CAT and GPX, and promote the expressions of SOD1, CAT, GPx1, p53 and Bax genes and inhibit the expression of Bcl-2 gene, leading to a higher ratio of Bax/Bcl-2 . Taken together, CYN may induce ROS overproduction, leading to increased p53 expression and ultimately promoting VSMC apoptosis. Therefore, the present study demonstrates that CYN could impair VMSCs, leading to vascular developmental defects and angiocardiopathy.